The Influence of the Independent Board of Commissioners and Corporate Sustainability on Firm Value in Mining on the Indonesia Stock Exchange (IDX) in 2021-2022 - Nur'Illiyyien; Fratiwi, Sri Ayu; Tikupasang, Medyoto; Fitriani; Jamaluddin; Habbe, Abdul Hamid; Mediaty (AFEBI Accounting Review, 2023)
Abstract This research aims to examine the effect of the independent board of commissioners and corporate sustainability on firm value. This research uses a causality quantitative approach. The research data is secondary data taken from the IDX data website. The sample used amounted to 15 mining sector companies during the two-year observation period. Purposive sampling is a technique used for data collection. The analysis method used is linear regression analysis with SPSS 23 analysis tool. The results showed that the independent committee and corporate sustainability have a significant influence on firm value. Keywords: Independent Board of Commissioners, Corporate Sustainability, Firm Value